Does Ultrasound Really Good Enough to Evaluate the Pneumothorax in the Emergency Department - Atilla Temel (17788481) (2023)
Thorax computed tomography in patients with thoracic trauma is undeniably a highly beneficial method. However, it also has disadvantages such as difficulties in transferring critical patients to computed tomography, delays in diagnosis, the risk of radiation exposure, and higher costs. On the other hand, ultrasonography can be rapidly performed at the bedside and is a non-invasive technique that poses no risk of radiation exposure. These advantages make it a valuable method in the early diagnosis of thoracic trauma. Therefore, this study aimed to provide insights into the sensitivity and accuracy of bedside ultrasonography in diagnosing pneumothorax in patients presenting with thorax trauma in an emergency department. The study sample comprised 132 patients over 18 years of age who were transferred with thorax trauma to the Emergency Clinic of Bakırköy Dr. Sadi Konuk Training and Research Hospital between January 30, 2015, and June 30, 2015. Ultrasonographic examinations were performed before thoracic computed tomography in all patients for whom a thorax computed tomography was indicated based on the clinical examination by the emergency room physician. The thoracic computed tomography reports, interpreted by a radiologist who was blinded to the ultrasonographic and clinical findings of the patients, were accepted as the gold standard. All 132 patients included in the study underwent Thorax ultrasonography. The average age of the patients was 76.5%, with the youngest patient being 18 years old and the oldest one being 90 years old. Of the patients, 45.38% (n = 101) were men. The results of Thorax ultrasonography showed that 19 patients had pneumothorax. These findings were then compared with the Thorax computed tomography results accepted as the gold standard. The results revealed that Thorax ultrasonography had a sensitivity of 56.2% and a specificity of 99% in detecting pneumothorax. According to the grading on CT, our observation revealed that the sensitivity of ultrasonography to detect pneumothorax increased proportionally with the severity of pneumothorax detected on thoracic computed tomography. The sensitivity of ultrasonography in patients with a grade 2 pneumothorax and those with a grade 3 pneumothorax, according to Thorax computed tomography, was found to be 70% and 100%, respectively. Thorax ultrasonography is a useful technique with high specificity in diagnosing pneumothorax, but its sensitivity decreases significantly when the size is below 1 cm. Other Information Published in: Indian Journal of Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12262-023-03895-w